Effects of Pulsed Electric Field (PEF) Processing on the Physical, Chemical and Microbiological Properties of Red-Fleshed Sweet Cherries (Prunus avium var. Stella) - Sotelo, Kristine Ann (Auckland University of Technology, 2015)
The effects of mild or moderate intensity pulsed electric field (PEF) processing on the chemical, flavor and microbiological properties of Stella sweet cherries were studied. The specific aims of this study were to determine (1) the effect of different PEF treatments on the physico-chemical properties of cherry samples, (2) the effects of different PEF treatments and storage conditions on the volatile profile of cherry samples, (3) the effects of different PEF treatments and storage conditions on the extraction or release of bioactive compounds including the anthocyanins and polyphenols on PEF-treated samples, and finally (4) the growth of probiotic bacteria specifically the lactic acid bacteria on PEF-treated cherry samples, The cherry samples were treated at a constant pulse frequency of 100 Hz and a constant pulse width of 20 μs with different electric field strengths between 0.3 and 2.5 kV/cm used. Cherry fruits used in this study that were subjected to PEF processing were analysed (1) immediately after PEF (S2) and (2) 24 hours of incubation at 4 °C (S3). PEF treated samples were significantly different to control sample in terms of juice yield, pH, titratable acidity (TA), total soluble solids (TSS) and moisture content (MC). There was a significant increase in juice yield in all PEF-treated samples compared to control. The pH values of samples incubated for 24 hours after PEF (S3) significantly increased compared to control and samples immediately after PEF treatment (S2). On the other hand, the values of TA and TSS significantly decreased for most S3 samples compared to the control and S2 samples. It was observed that as the intensity of PEF treatments increased, the TSS value also increased for S3 samples. In terms of flavour volatiles, S3 samples generated higher concentrations of volatiles than S2 samples. The moderate intensity applied to the samples induced higher amounts of volatile compounds characteristic of cherry flavour. In addition, with the low energy intensities applied, no undesirable compounds were detected for all samples. In terms of anthocyanins, only cyanidin glucoside was significantly affected by PEF treatments. S3 samples had significantly higher cyanidin glucoside content compared to most S2 samples. A contrasting trend to anthocyanins was observed for polyphenols. Only four compounds, namely rutin, 4-hydroxybenzoic acid, isorhamnetin rutinoside, and myricetin, were significantly affected by storage and PEF treatments. S2 samples generated higher content of rutin, 4-hydroxybenzoic acid and isorhamnetin rutinoside compared to S3 samples. On the other hand, myricetin was the only compound that was significantly higher in S3 samples than S2 samples. Overall, the growth of LAB in cherries was affected by the different PEF treatments. Stimulatory (more nutrients were released after PEF application) effects by PEF were observed on samples immediately after PEF application (S2) which means the LAB count was positively increased while, inhibitory effects was observed for samples incubated for 24 hours after PEF (S3) which resulted in a decrease in LAB counts. Overall, it can be concluded that the application of mild or moderate PEF intensities influenced chemical, microbiological and flavour characteristics of cherries. The findings from this study offer both methodological and practical contributions. The use and capability of PEF processing in terms of extracting valuable components of cherries that included flavour volatiles and bioactive compounds have been demonstrated. Hence this study would provide the food processors with a technological edge when using a non-thermal processing method, like PEF in meeting the current consumer demand for minimally-processed and fresh-like food products.
Keywords: Pulsed electric field; Sweet cherry fruit; Flavour profile